Amphibians and Reptiles of the Tirimbina Biological Reserve: a baseline for conservation, research and environmental education in a lowland tropical wet forest in Costa Rica - Branko, Hilje (2020)
The Tirimbina Biological Reserve is located in the lowlands on the Atlantic versant of Costa Rica. This study provides an updated comprehensive herpetofauna species list and summarizes the results of all the herpetofauna research conducted at Tirimbina over the last ten years (2009–2019) across various microhabitats, both daytime and nighttime. We also added historical records from occasional sightings and reports from researchers, staff, visitors, interns, fellows, and volunteers since the 1990’s. We found 52 amphibian and 78 reptile species on the reserve, including a few species considered at–risk according to the IUCN Red List. We conclude that Tirimbina is a herpetofauna biodiversity hot spot in Costa Rica because it provides unique habitat characteristics for a variety of species, including habitat for both forest and forest–edge specialists.